Comparison of von Willebrand factor (VWF) activity levels determined by HemosIL AcuStar assay and HemosIL LIA assay with ristocetin cofactor assay by aggregometry. (14th April 2016) - Sagheer, S.; Rodgers, S.; Yacoub, O.; Dauer, R.; Mcrae, S.; Duncan, E.
Abstract : Introduction: Diagnosis of von Willebrand disease (VWD) requires quantitative as well as qualitative determination of von Willebrand factor (VWF) levels. For functional assessment of VWF, ristocetin cofactor assay by aggregometry is considered to be the gold standard. However, need for technical expertise, labour intensiveness, difficult standardization and high intra‐ and inter‐ assay variabilities are some of the limitations of this methodology. Various assays for determination of VWF adhesive function using different methodologies have been developed in recent years. Aim: To evaluate the HemosIL AcuStar chemiluminescence assay (VWF:RCo[Acu]) and the HemosIL latex immunoassay (VWF:act) as diagnostic tests for VWD and identification of type 2 VWD in comparison with the ristocetin cofactor assay performed by aggregometry (VWF:RCo[Agg]). Methods: Results from 96 samples analysed by VWF:RCo[Acu] and 128 samples by VWF:act were compared with VWF:RCo[Agg]. Sixty of these samples (25 normal, 17 type 1 and 18 type 2) were analysed by all three assays. Results: VWF:RCo[Acu] showed excellent agreement with VWF:RCo[Agg], and readily identified all type 2 VWD samples tested. VWF:act showed reasonable agreement with VWF:RCo[Agg] for most patients, but had a slightly lower sensitivity for detection of type 2 VWD. Conclusion: VWF:RCo[Acu] assay has the potential to replace VWF:RCo[Agg] for the diagnosis of VWD.